The Effect of Brain Game Puzzle Intervention on Cognitive Function in Elderly Residents at the Karawang Social Rehabilitation Center for the Elderly - Jessy Maretha Tiocosby; Naufal Zaidan Akram; Aprilina Sartika (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Elderly individuals are vulnerable to cognitive decline due to aging, which affects memory, attention, and executive functions. This study aimed to evaluate the effect of Brain Game Puzzle intervention on cognitive function among elderly residents at the Karawang Social Rehabilitation Center for the Elderly (PRSLU). A pre-experimental one group pretest-posttest design was applied to 31 elderly participants selected by purposive sampling. The intervention involved Puzzle games conducted twice weekly for three weeks, with each session lasting 30 minutes, and cognitive function was assessed using the Mini Mental State Examination (MMSE). The Wilcoxon test showed a significant improvement in cognitive function post-intervention (p=0.001), with the proportion of elderly with severe cognitive impairment decreasing from 87.1% to 41.9%. These findings support the neuroplasticity theory that cognitive stimulation can maintain and enhance brain function in the elderly. This study implies that Brain Game Puzzle is an effective, low-cost, and easily applicable non-pharmacological intervention that can be implemented routinely in elderly care facilities to prevent cognitive decline.